1991
DOI: 10.2337/diab.40.1.134
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Deterioration of Endocrine Function After Intraportal but Not Kidney Subcapsular Rat Islet Transplantation

Abstract: In inbred streptozocin-induced diabetic rats, the long-term function of different endocrine pancreatic isografts was compared. Isolated islets transplanted into the portal vein showed a progressive deterioration of function over time. In contrast, islets under the kidney capsule sustained a constant long-term function controlling all clinical signs of diabetes. Recipients of kidney subcapsular islets displayed normal growth rate, peripheral serum glucose and insulin levels, and metabolic parameters. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
3

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 16 publications
1
21
3
Order By: Relevance
“…It could be hypothesized that grafted LP-islets would not decrease the high glycemia of diabetic recipient rats while NP ones would be more effective; however, this was not observed. It has been shown that a simple islet transplantation of a short duration, up to 5 days, and independent of islet number did not correct the hyperglycemia of STZ diabetic rats; however, long-term islet grafts promote fed-state normoglycemia depending on the site of the transplantations [31][33].…”
Section: Discussionmentioning
confidence: 99%
“…It could be hypothesized that grafted LP-islets would not decrease the high glycemia of diabetic recipient rats while NP ones would be more effective; however, this was not observed. It has been shown that a simple islet transplantation of a short duration, up to 5 days, and independent of islet number did not correct the hyperglycemia of STZ diabetic rats; however, long-term islet grafts promote fed-state normoglycemia depending on the site of the transplantations [31][33].…”
Section: Discussionmentioning
confidence: 99%
“…Intrahepatically transplanted islets may also be lost as a result of localised, insulin-induced hepatic steatosis, lipotoxicity and inflammation [15]. These influences can damage the islets, and long-term studies have identified the non-immune-mediated loss of function from intrahepatically transplanted islets [16]. Research continues to increase the success rate of portal delivery; however, the local milieu of intrahepatically delivered islets cannot be readily manipulated and provides a significant challenge to substantive improvements.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous sites have been investigated as an ideal islet implantation site, including the kidney subcapsule (6, 7), liver (6-8), peritoneum (8, 9) omental pouch (10), skeletal muscle (9, 11), subcutaneous tissue (8, 11), and spleen (6). However, it is difficult to determine the ideal implantation site based on these published data because of the variety of donor islets (fetal islet-like clusters vs. adult islets), the species of donor and recipients (rat, mouse, and pig), the parameters used to determine the success of implantation (metabolic control, oxygen tension, or functional mass) and the number of sites compared.…”
Section: Introductionmentioning
confidence: 99%